UNLOCK YOUR CREATIVITY WITH PHOTOPEA edit and retouch images, and create striking text and designs with the free online software - Burton, Michael (Packt Publishing Ltd., 2024)
Tap into the power of Photopea and learn photo editing, digital painting, and how to design graphics for social media, marketing, and merchandise with this self-paced manual Key Features Gain foundational skills in photo editing, design, and digital painting Discover tools for selections, color adjustments, text application, and content creation Explore the latest updates and plug-ins for more control over image enhancement Purchase of the print or Kindle book includes a free PDF eBook Book Description Photopea is a comprehensive image and photo editing design tool that provides essential features and capabilities comparable to Adobe Photoshop. This book covers the latest version of Photopea, featuring step-by-step instructions for image editing, improving and enhancing designs with text and effects, and creating eye-catching projects for print and the web. The first part of this book will teach you how to navigate the workspace, use the best tools for specific tasks and projects, and make perfect selections. You'll also discover how to remove backgrounds, merge and/or add objects, and adjust colors to create impressive images. Later, you'll explore layers and compositing techniques, and get hands on with retouching images like a pro. The book will demonstrate how to create collages and use brushes, color wheels, and swatches for drawing and painting. You'll also learn how to apply impressive text to images to create posters, flyers, and logos. By the end of this book, you'll have learned how to retouch, paint, enhance, and manipulate images; how to use templates provided by Photopea; and finally, how to apply your skills to projects. What you will learn Understand how to use masks, layer adjustments, and work non-destructively with your images Use photo retouching techniques to enhance your images, revive old photos, and apply effects Use brushes effectively and learn how to create custom brushes for specific tasks and effects Apply different selections for removing backgrounds and objects from photos Utilize the principles of color theory to craft visually stunning compositions Draw stunning vector and bitmap formats for coloring, rendering, and finished illustrations Who this book is for This book is for photographers, illustrators, graphic designers, hobbyists, and students in need of alternative graphic design software suitable for digital imaging and more. Beginners with no prior knowledge of photo editing will also benefit from this book, as it will help them learn fundamental editing skills while they explore Photopea's functionality.
Keywords: Photopea; Photography -- Digital techniques; Image processing -- Digital techniques; Computer graphics; Photographie numérique; Traitement d'images; Techniques numériques; Infographie; digital imaging; computer graphics